Communication and Mass Vaccination Strategies After Pertussis Outbreak in Rural Amish Communities—Illinois, 2009–2010. Issue 4 (25th March 2013) - Medina‐Marino, Andrew; Reynolds, Debra; Finley, Carol; Hays, Susan; Jones, Jane; Soyemi, Kenneth
Abstract Purpose During January 2010, 2 infants from an Amish community in east‐central Illinois were hospitalized with pertussis. The local health department (LDH) intervened to control disease transmission, identify contributing factors, and determine best communications methods to improve vaccination coverage. Methods A retrospective cohort study was conducted using public health surveillance data to determine the extent of the outbreak; the standard Centers for Disease Control and Prevention and Council of State and Territorial Epidemiologists case definition for pertussis was used. The standardized Illinois Department of Public Health pertussis patient interview form was used to collect demographic, symptom, vaccination history, and treatment history information. To control disease transmission, LDH staff worked with the Amish community to promote a vaccination campaign during February 6–April 30, 2010. Findings Forty‐seven cases were identified, with onsets during December 2009–March 2010. Median age was 7 (interquartile range 1–12) years. Nineteen (40%) patients were male; 39 (83%) were aged <18 years; 37 (79%) had not received any pertussis‐containing vaccine. Presenting symptoms did not differ substantially between vaccinated and unvaccinated patients. Duration of cough was longer among unvaccinated than vaccinated patients (32 vs 15.5 days, P = .002). Compared with vaccinated patients, proportionately more unvaccinated patients reported secondary household transmission (30% vs 72%; P = .012). Through enhanced vaccination campaigns, 251 (∼10%) Amish community members were administered 254 pertussis‐containing vaccines. Conclusions Targeted health communication and outreach resulted in a successful vaccine campaign and long‐running monthly vaccination clinic. Amish do not universally reject vaccines, and their practices regarding vaccination are not static.